L'uomo tutto intero Biografia di Carlo Livi, psichiatra dell'Ottocento - Martina Starnini (Premio Tesi di Dottorato, 2018)
This volume reconstructs Carlo Livi (1823-1877)'s biography, focusing on his medical and psychiatric work and on his path as a man and intellectual who lived during the Italian Risorgimento. Livi was a key figure in Italian psychiatry, halfway between the therapeutic optimism of the early 19th century and the pessimism of post-Darwinian psychiatry, both in the practical aspects and in the theoretical elaboration. The study highlights how, in this case, the moral treatment applied by 19th century psychiatry throughout Europe is linked to the events of the Italian Risorgimento. The moralizing and educational request, as well as the anthropological study of the human being, were aimed at the sick, the insane, at children, at criminals and the Italian people in order to carry out a national and secular project of social regeneration in Italy.